La diversidad étnica en la constitución de la sociedad romana en Eneida: El caso de los Sabinos - de Santis, Guillermo (2012)
In Virgil's Aeneid ethnic diversity is fundamental to understanding the formation of Roman society at the time of Augustus. From a broad historical and mythographic material Virgil relocates various Italic peoples in the geography of the Latium and reconstructs a history of relationships between these peoples and Trojans from which one can understand the presence of different ethnic groups have in Roman society after the Bellum Sociale. In this paper we take the example of the Sabines to show ethnographic criteria defined in the Aeneid and from which, it justifies its prestigious status in Roman society of the late first century.